The N-terminal Region of Nisin Is Important for the BceAB-Type ABC Transporter NsrFP from Streptococcus agalactiae COH1 - Reiners, Jens; Lagedroste, Marcel; Ehlen, Katja; Leusch, Selina; Zaschke-Kriesche, Julia; Smits, Sander H. J. (Frontiers in Microbiology, 2017)
Lantibiotics are (methyl)-lanthionine-containing antimicrobial peptides produced by several Gram-positive bacteria. Some human pathogenic bacteria express specific resistance proteins that counteract this antimicrobial activity of lantibiotics. In Streptococcus agalactiae COH1 resistance against the well-known lantibiotic nisin is conferred by, the nisin resistance protein (NSR), a two-component system (NsrRK) and a BceAB-type ATP-binding cassette (ABC) transporter (NsrFP). The present study focuses on elucidating the function of NsrFP via its heterologous expression in Lactococcus lactis. NsrFP is able to confer a 16-fold resistance against wild type nisin as determined by growth inhibition experiments and functions as a lantibiotic exporter. Several C-terminal nisin mutants indicated that NsrFP recognizes the N-terminal region of nisin. The N-terminus harbors three (methyl)-lanthionine rings, which are conserved in other lantibiotics.